2021
DOI: 10.1002/ags3.12432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of thoracic duct lymph node metastasis in esophageal squamous cell carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Metastatic TDLNs were observed on the same or cranial level of the primary lesion in most patients with TDLN metastasis. Because this trend was consistent in our follow-up study with an expanded cohort and longer follow-up duration, 20 those results suggest that the lymphatic route along the TD, which runs from the caudal to the cranial side, seeds the cancer cells to the TDLN. The presence of TDLN was also confirmed in a cadaver study, which discovered TDLN in six of seven cadavers (86%), with a median number of 1 (range, 0–6).…”
Section: Ln Metastatic Patterns For Ecsupporting
confidence: 85%
See 1 more Smart Citation
“…Metastatic TDLNs were observed on the same or cranial level of the primary lesion in most patients with TDLN metastasis. Because this trend was consistent in our follow-up study with an expanded cohort and longer follow-up duration, 20 those results suggest that the lymphatic route along the TD, which runs from the caudal to the cranial side, seeds the cancer cells to the TDLN. The presence of TDLN was also confirmed in a cadaver study, which discovered TDLN in six of seven cadavers (86%), with a median number of 1 (range, 0–6).…”
Section: Ln Metastatic Patterns For Ecsupporting
confidence: 85%
“…In our previous study that evaluated the long-term outcomes in patients who had TDLN metastasis, the recurrence-free survival and overall survival of patients with TDLN metastasis were almost identical to those with positive LN metastasis in extraregional LNs such as supraclavicular LNs. 20 Ohkura et al investigated the EI of TDLN. Their results showed that in ECC patients with cT3–4, there was no statistically significant difference in EI between TDLNs and non-TDLNs.…”
Section: Surgical Approach To Eradicating a Wide Range Of Ln Metastas...mentioning
confidence: 99%
“…Figure 1 summarizes the distribution of TDLN metastasis based on primary tumor location, demonstrating that TDLN metastasis tends to occur at the same level as the primary tumor or cranial it. This finding was confirmed in a follow-up study conducted by the same institution using a larger cohort, 12 , 13 which revealed that the lymphatic route along the TD could extend from caudal to cranial levels. In terms of prognosis, recurrence-free survival (RFS) and overall survival (OS) were significantly worse in patients with TDLN metastasis, which was shown to be an independent prognostic factor in the multivariate analysis.…”
Section: Oncological Impact Of Td Resection In Esophageal Cancer Surgerymentioning
confidence: 53%
“…Subsequently, we investigated the presence and metastatic rate of TDLN in esophageal cancer surgery. 12 , 13 As shown in Table 1 , the average number of TDLNs, including nonmetastatic nodes, was comparable across studies; this was confirmed in a cadaver study revealing the presence of TDLNs in six of seven cadavers (86%). 14 In our study, TDLN metastasis was observed in 7% of patients with surgically resectable ESCC, similar to the finding of a previous study.…”
Section: Oncological Impact Of Td Resection In Esophageal Cancer Surgerymentioning
confidence: 56%
“…The effects of nCRT on the number of collected LNs could be one reason for this finding. Previous studies suggested that nCRT may sterilize micrometastases because it removes fewer LNs at dissection than surgery alone for ESCC patients [ 12 , 24 ]. Moreover, less recurrence was observed in the high e-LNS group.…”
Section: Discussionmentioning
confidence: 99%